Revisiting Raktarsha Chikitsa Through Jalaukavacharana: An Evidence Based Ayurvedic Perspective (International Journal of Environmental Sciences, 2025)
Background: Raktarsha (bleeding piles) is one of the most common Gudagata Vikaras that severely affects the quality of life through persistent bleeding, pain, and discomfort. Despite the availability of multiple treatment modalities in Ayurveda—Bheshaja, Kshara, Agni, and Shastra Karma—there is a rising need for minimally invasive and effective approaches. Jalaukavacharana (leech therapy), a form of Raktamokshana, holds promise in Raktarsha Chikitsa due to its Shothahara, Vedanasthapana, and Raktashodhana properties. This review reanalyzes classical insights and clinical evidence supporting the efficacy of Jalaukavacharana in the management of Raktarsha. Aim: To reevaluate the role of Jalaukavacharana in Raktarsha Chikitsa by integrating classical Ayurvedic principles with modern evidence based research. Objectives: To explore the classical references and rationale of using Jalaukavacharana in Raktarsha To assess clinical outcomes and mechanisms of action from recent evidence To suggest an integrative therapeutic model based on Ayurvedic and biomedical insights Materials and Methods: An extensive review was conducted on classical Ayurvedic texts including Sushruta Samhita, Ashtanga Hridaya, and Chakradatta, along with a systematic search of published clinical trials and research articles from databases like PubMed, AYUSH Research Portal, and Google Scholar. Both observational and interventional studies evaluating Jalaukavacharana for hemorrhoidal disorders were included. Results: Classical texts emphasize Jalaukavacharana as a preferred Raktamokshana method for Raktaja Vikaras. Recent clinical studies have demonstrated significant reduction in bleeding, pain, swelling, and recurrence rate of Raktarsha following repeated sittings of Jalaukavacharana. The antiinflammatory and anticoagulant properties of leech saliva components like hirudin and calin corroborate traditional claims. Conclusion: Jalaukavacharana emerges as a safe, effective, and evidence based Ayurvedic intervention in the management of Raktarsha. Integrating this traditional therapy into modern proctology could provide a holistic and patient friendly approach, especially in chronic and recurrent cases.